Electricity ( supply) act, 1948 ( act no. 54 of 1948) - India. Ministry of Law and Justice (New Delhi, 1995)
This edition of the Motor Transport Workers Act, 1961 is being published in diglot form. The English text and the authoritative Hindi text of the Act have been modified up to the 1st day of October, 1994
Keywords: Power supply act-India-1948